THEOLOGY OF LIBERATION IN THOUGHT OF ALI SHARI’ATI - Adhan, Syamsu Rijal (Journal of Islam and Science, 2016)
This paper discusses about the theological thought of Ali Shariati, more precisely  pertaining to the concept of liberation theology. Sub discussions in this paper comprise the biography of Ali Shariati, a list of languages to understand Ali Shariati’s thought and language expressions, Ali Shariati’s world view and ideology, world view Tawhid (theology) that liberates, and the philosophical concept of the creation of man. Ali Shari’ati understands religion not in a ritual dimension only. According to him, religion is the source of awareness, the cornerstone of ethics (morality), responsibility,  and free will that is capable to mobilize its followers into a force of liberation from determination of multitheism ideologies that oppress. Tawhid is the foundation of liberation ideologies that negate all forms of discrimination to move towards egalitarianism (equality) of human beings. Tawhid is the spirit of resistance against tyranny and oppression, based on the values of justice. In the view of Ali Syariati, Tawhid is the ephisentrum of life and mode of existence. Tauhid necessitates teocentric world view leading men in motion of existential evolution to become teomorphis human, men the characteristic of divine attributes.